Haematological and Biochemical Studies on some Species of Fishes - LC Chuku; AA Uwakwe (Journal of Applied Sciences and Environmental Management)
In this study the following biochemical and haematological studies on Catfish (clarius gariepianus); Mullet (Mugi Cephalus), Tilpia (Oreochromis niloticus), mudskipper (Gobi I), African sleeper (Gobi-II), were carried out; Haemmoglobin electrophoresos, ABO Blood grouping and Glutathine-S-Transferase (GST) activity. Catfish haemoglobin electrophoretic pattern was similar to human HbAA blood, with haemoglobin (Hb) concentration range of 12.0 – 17.8gm%. About 50% of catfish indicated the Rh.D- while thew remaining 50% indicated the Rh.D+ blood group/. The ‘A’ ‘O’ and ‘AB’ blood groups were detected and glutathione-Stransferase activity values of 5.64 – 7.27 I.U were obtained. Haemoglobin electrophoresis of mullet gave a pattern similar to HbCC of human blood. Hb concentration values were of the range of 5.5 -10.7gm% blood group results gave values of 50% D+ (A,O) and 50% (AB). GST activity values of 13.50-20.10 I.U were obtained. Gobi-I and Gobi-II Hb electrophoretic pattern was similar to human HbSS blood with Hb concentration range of 1.8-5.57gm%. GST activity values of 16.97-33.08 I.U. were obtained. Haemoglobin electrophoresis of Tilapia produced multiple patterns corresponding to human HbSS, HbCC and possibly HbCD. Hb concentration values were of the range of 3.70-12.94gm% and GST opf 9.90-12.92 I.U were obtained. Only the ‘O’ and ‘AB’ blood groups were identified.